Behaviour of expanded piles in clay under uplift and compressive loading - Alimohammadi, Payman (2014)
Existing soil at construction site may not always be suitable for supporting structures. Hence, various techniques can be utilized to improve the shear strength, increase the bearing capacity, increase the factor of safety, and reduce the settlement, shrinkage and swelling of soft soils. Among the improvement techniques, preloading and radial preloading using prefabricated vertical drainage are two popular methods in order to improve soft soils. Recently, a new concept of radial preloading has been presented under the name of expanded piers or expanded piles. In this method, an expandable membrane is expanded by means of an injection of air pressure to make an expanded cylindrical cavity, and is filled with a suitable material such as concrete or sand. Thus, the expanded element and the surrounding soil provide a stiffer component compared to the untreated soil. The main focus of this study was an evaluation of the effect of the diameter ratio (DR= final diameter of membrane after expansion / initial diameter of membrane before expansion) on the load capacity of the pile under upward and downward loading. To achieve these aims, 18 physical modelling tests on white Kaolinite were carried out to determine the pile pull out capacity and bearing capacity of the piles. Hence, the diameter ratios of 1.5, 2 and 2.5 times the initial diameter of the cylindrical cavity were selected. In this study, two methods were used to perform the expanded piles, radial expansion and radial expansion with surcharge. A series of physical modelling was designed to assess the different behavior of these two methods. In addition, a series of numerical modelling, based on the soft soil and Mohr-coulomb model, were conducted to simulate the pile behaviour and verification of the laboratory results. Based on the obtained results in the pull out tests, a significant increase was observed in the load capacity equal to 86%, 132% and 153%, for diameter ratios equal to 1.5, 2, and 2.5, respectively, in the soft clay for expansion method. The increase in load capacity were equal to 170%, 175% and 183% for the same diameter ratios, performed by means of expansion with surcharge method. Similarly, in the cases of compressive loading, the load ratios were increased equal to 40%, 47% and 53%, for diameter ratios equal to 1.5, 2, and 2.5, respectively, for expansion method. The increase in load capacity were 99%, 82% and 69% for the same diameter ratios, performed by means of expansion with surcharge method. Moreover, results showed that with increase in the piles diameter equal to 33% and 66%, the load ratios were increased up to 46% and 86%, for expansion method in case of pull out tests. Meanwhile, the load capacities were increased up to 63% and 144% for the expansion method in case of compressive tests. Furthermore, the soft soil model can be considered to have good agreement to simulate pile behaviour under vertical loading with the effect of radial preloading.